The Effect of Electrode Gap on the Nucleation of CaCl2.6H2O by using Sharp End Copper Electrode - Risky Afandi Putri; Ahmad Swandi; Annisa Rahman; Radhiah Anggraeni; Inge Magdalena Sutjahja; Daniel Kurnia (Universitas Ahmad Dahlan, 2022)
The performance of the calcium chloride hexahydrate (CaCl2.6H2O) to store the sensible and latent heats is mainly determined by its nucleation or liquid to the solid phase transition. This is due to the barrier that has to be overcome when the material undergoes the nucleation process with a reduction in the entropy value. This material, with melting temperature around 29.8 Â°C, can be used as the thermal energy storage for building applications in tropical areas such as Indonesia, in order to reduce the electrical energy for aircond (AC) machines. In this paper, we report the results of an experimental study for the effect of the electrical field to the supercooling degree and time period for a phase transition. The variation in the magnitude of the electrical field was achieved by variation in the gap of the electrode for sharp end electrodes (cathode and anode), for the commonly sold copper electrode.